SUSTAINABLE DEVELOPMENT OF THE ALBANIAN ECONOMY, COMPARATIVE ANALYSIS OF SME GROWTH RATES - Çelo, Evis; Dumi, Alba; Çelo, Jonil (European Scientific Journal, ESJ, 2015)
In this paper we will precisely focus on the definition of SME and their ability to build a business plan that will help them to be successful in terms of seeking funds. For this reason, SME and their financing opportunities in our country is one of the issues that we will treat. Firstly, we will treat the business plan in theory and its role on SME, and is being build a business plan for a Travel Agency. In this paper, firstly we stop on the study of literature on SME concept and the business plan. For this reason we have found valid date information on studies from various writers and publications in foreign newspapers, as well as the publications of Prof. Alba Dumi "Entrepreneurship and small business management" as well as studies of different authors. By giving a financial view on SME over Albania, we have received information from bulletins of the Albanian Bank. I have contact with different banks in Albania, and especially with the employees of Raiffeissen Bank.